2018
DOI: 10.15406/jdhodt.2018.09.00412
|View full text |Cite
|
Sign up to set email alerts
|

Salivary parameters among chronic alcoholics and non-alcoholic males in Ambala, Haryana - a comparative study

Abstract: The study was conducted among patients visiting the outpatient Department (OPD) of Public Health Dentistry, M.M college of Medical Sciences and Research, Mullana to correlate the salivary parameters in male alcoholics and non-alcoholics between 18-49 years of age in Ambala District Haryana and to calibrate salivary parameters-pH, buffering capacity and salivary flow rate in chronic alcoholic and non-alcoholic male subjects. Ethical approval from the institutional ethical committee (IEC) was taken and written i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is currently accepted that age, gender and ethnicity play a role in the development of AUD ( Gupta et al, 2018 ; National Institutes of Health, 2021a ) and in discovery of biomarkers ( Tarallo et al, 2018 ; Rosato et al, 2019 ). However, the progress of human civilization now blurs ethnic, gender and age divisions, which thus become less and less relevant.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently accepted that age, gender and ethnicity play a role in the development of AUD ( Gupta et al, 2018 ; National Institutes of Health, 2021a ) and in discovery of biomarkers ( Tarallo et al, 2018 ; Rosato et al, 2019 ). However, the progress of human civilization now blurs ethnic, gender and age divisions, which thus become less and less relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non- alcoholic patients, alcoholic ones, in the present study and other studies [ 1 , 37 ], had worse oral health indices. Gupta and coworkers [ 38 ] showed lower salivary flow rate and PH in alcoholics than non-alcoholics, which could be the reason for their poor oral health. Similar to Santo and coworkers' study [ 30 ], we also found worse oral health indices in patients addicted to smoked/injected illegal drugs.…”
Section: Discussionmentioning
confidence: 99%